Integrating Students’ Real-Time Gaze in Teacher–Student Interactions: Case Studies on the Benefits and Challenges of Eye Tracking in Primary Education - Raimundo da Silva Soares; Eneyse Dayane Pinheiro; Amanda Yumi Ambriola Oku; Marilia Biscaia Rizzo; Carolinne das Neves Vieira; João Ricardo Sato (Applied Sciences)
Integrating neuroscience techniques, such as eye tracking, into educational practices has opened new avenues for understanding the cognitive processes underlying learning. This study investigates the feasibility and practicality of using eye tracking as a supportive tool for educators in primary school settings. By taking into account eye-tracking features in lesson plans and instruction, this study explores the benefits and challenges of this technology from teachers’ perspective. The findings reveal that eye tracking can enhance interactivity, maintain student attention, and provide immediate feedback, thereby aiding in identifying student difficulties that may otherwise go unnoticed. However, the study also highlights concerns related to technical complexities, data privacy, and the need for teacher training to utilize and interpret eye-tracking data effectively. These insights contribute to a nuanced understanding of how eye-tracking technology can be implemented in educational settings, offering potential pathways for personalized teaching and improved learning outcomes.